Factors that influence the use of health services by young people. Case of Jorge Tadeo Lozano University, Bogotá headquarters - Quiroga-Otálora, Yorley; González-Támara, Leandro (Universidad y Salud, 2019)
Introduction: Based on the Colombian Constitution, universities have the autonomy to develop their own healthcare service programs. Objective: To determine the factors by which young people use the healthcare services provided by the Jorge Tadeo Lozano University. Materials and methods: Using a 26-question survey, we interviewed students aged between 16 to 27 years, who have used the university healthcare facilities at least once during the period of January 13 to July 31 2017. Results: The key factors for using healthcare services were cost, habits, health professionals, environment and health promotion and prevention campaigns. Conclusion: A university policy that promotes the use of medical assistance programs provided by educational institutions encourages the establishment of a self-care culture and a structural change in the development of a healthy student lifestyle. A change that does not exclude students from using the General Social Security in Health System.